Chronological Picture-Based Storytelling to Improve Understanding of Dual Simultaneous Instructions in Early Childhood - Alwia Alwia; Supian Azhari (Journal of Early Childhood Education Research, 2026)
Purpose: This study aimed to improve the language development of children aged 4–5 years, specifically their ability to understand and execute two simultaneous instructions, through chronological picture-based storytelling activities in Group A of TK Pertiwi VII Saruran. Methodology: A Classroom Action Research (CAR) design was employed, consisting of two cycles, each incorporating four phases: planning, implementation, observation, and reflection. The study involved 10 children (aged 4–5 years) in Group A. Data were collected through structured observation checklists using a four-point developmental scale: Not Yet Developed (BB), Beginning to Develop (MB), Developing as Expected (BSH), and Developing Very Well (BSB). Classical mastery was set at 80%. Results: In Cycle I, 50% of children (5 out of 10) achieved the mastery threshold. Following instructional refinements in Cycle II (simplification of instruction syntax, integration of commands into story dialogue, and progressive scaffolding), the mastery rate increased to 80% (8 out of 10), meeting the classical mastery criterion. Conclusions: Chronological picture-based storytelling is an effective instructional strategy for enhancing the receptive language development of early childhood students. The integration of sequential visual cues with narrative commands provides a structured, engaging, and contextually meaningful scaffold for dual-instruction comprehension. These findings contribute to early childhood language pedagogy and support the use of culturally relevant, visual storytelling as a differentiated instructional tool.